Perbandingan Kualitas Hidup Pasien Hemorhoid Sebelum dan Sesudah Laser Hemorrhoidopexy (LHP) di Rumah Sakit Sekunder Multisentra Jakarta - Megatia, Ika (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Laser hemorrhoidopexy (LHP) is a minimally invasive technique increasingly used for hemorrhoid management. This retrospective cohort study evaluated changes in HEMO-FISS-QoL scores among patients with internal hemorrhoids, with or without external components, before and after LHP. Patients completed the questionnaire pre-procedure and at 2 and 6 weeks post-procedure. Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc testing. A total of 69 patients were included, with a mean age of 40 ± 13 years; 42 (60.9%) were female. The total HEMO-FISS-QoL score significantly decreased from baseline to 2 and 6 weeks after treatment (60.83 ± 4.11 vs. 27.01 ± 3.03 vs. 8.27 ± 2.95; p < 0.001). Significant improvements were also seen across all domains from baseline to 6 weeks: physical discomfort (61.89 ± 7.21 vs. 9.25 ± 5.06; p < 0.001), psychological impact (52.43 ± 5.49 vs. 4.15 ± 3.44; p < 0.001), defecation (79.84 ± 11.29 vs. 12.68 ± 6.66; p < 0.001), and sexuality (59.60 ± 12.53 vs. 12.32 ± 8.97; p < 0.001). In conclusion, LHP significantly improved patients’ quality of life across physical, psychological, defecation, and sexual domains, highlighting its effectiveness as a minimally invasive treatment for hemorrhoids. Keywords Hemorrhoids, laser hemorrhoidoplasty, quality of life, HEMO-FISS-QoL